PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS GAMBAR PADA MATERI STRUKTUR DAN FUNGSI JARIANGAN TUMBUHAN UNTUK SMP - Roswan, Wely Desta; Ardi, Ardi; Risdawati, Renny (Pendidikan Biologi, 2013)
ABSTRACTImages in learning biology is one medium that can explain abstract concepts into concrete in the material structure and function of plant tissue, and organ parts plant roots, stems, leaves, fruits and seeds. This was development research, which develop student worksheet based of image the structure and function of plant tissueÂ  that develop by 4-D models that have been modified, comprising the steps of define, design and develop. Â Worksheet produced very valid with a value of 90.8% validity LKS. LKS is also categorized the resulting practical, with a value of 85.30% practicalities of teachers and of students with practicalities value 92% categorized as very practical.Â